Method of identification of tree species composition of forests on the basis of geographic information database - Barabash, Oleh; Bandurka, Olena; Svynchuk, Olha; Tverdenko, Halyna (Національний технічний університет "Харківський політехнічний інститут", 2022)
Monitoring of the forests with the help of remote sensing of the Earth systems is actual on the present stage of people development. Existing systems of research do not allow to use geographic information databases and don't include the spectrum of exploration that are presented in our work. The aim of this article is to develop the method of identification of tree species composition of forests on the basis of geographic information database in the integration with correlation analysis. It will give the possibility to find the most negative things that influence on the condition of forest ecosystems and neutralize them at the first stage of their influence. Satellite images that are received from the satellites Landsat 5 and 8 are used to make the database. Tree species composition of Mozhariv forest during 20 years is analyzed as an example in this article. Classification of tree species composition of forests using space images is made on the basis of Bayes classifier. There is a special geographic information database for further data processing and identification of tree species composition is developed. Forest is analyzed on the number of trees in each species during continuous time measures (in 2000, 2010 and 2020) in this article. Results of the work are presented with the help of graphics. Correlation analysis, which helps to make the analysis of tightness of connections between changes trees in number and different forest criteria, is made to identify tree species composition of forest. Developed method together with well-known methods of monitoring of forests help us to make effective application for analysis of tree species composition of forest changes and to make better existing information systems including different quality demands. Peculiarity of developed information system is in using of the data processing module as a part of geographic information system and implementing correlation analysis with identification of factors that influence each other. It helps to increase quality in management and monitoring of forest resources. Geographic information becomes available for users.

На сучасному етапі розвитку суспільства актуальним є моніторинг лісових насаджень за допомогою дистанційного зондування Землі (ДЗЗ). Існуючі системи дослідження змін рослинності неефективно використовують геоінформаційної бази даних (ГБД) та не охоплюють спектр спостережень, розглянутих у даній роботі. Метою статті є розробка методу визначення породного складу лісових насаджень на основі геоінформаційної бази даних в інтеграції з кореляційним аналізом. Це дасть можливість виявляти найбільш негативні чинники, що впливають на стан лісових екосистем та нейтралізувати їх на початковій стадії впливу. Для створення бази даних використовуються космічні знімки, отримані від супутників Landsat 5 та 8. В якості прикладу проаналізовано лісовий покрив Можарівського лісництва за останні 20 років. Класифікація породного складу лісових насаджень за космічними знімками виконується на основі класифікатора Байєса. В роботі створена спеціалізована геоінформаційна база даних для подальшої обробки даних та встановлення породного складу. В роботі проаналізовано лісовий покрив за кількістю дерев по кожній породі окремо протягом тривалих часових рядів (2000, 2010 та 2020 роки). Результати досліджень мають графічне відображення. Для аналізу лісового покриву також проведено кореляційний аналіз, який визначає щільність взаємозв’язків між зміною кількості деревних насаджень та різними лісовими показниками. Розроблений метод разом з відомими методами моніторингу лісів дозволяють створити ефективне програмне забезпечення для аналізу зміни лісових насаджень та удосконалити існуючі інформаційні системи з урахуванням різних вимог до якості. Особливістю створюваної інформаційної системи є використання модуля обробки даних в складі геоінформаційної системи та проведення кореляційного аналізу з встановленням залежності факторів. Це сприяє підвищенню якості управління та моніторингу лісових ресурсів, доступності геоінформації для користувачів.
Метод визначення породного складу лісових насаджень на основі геоінформаційної бази даних
Keywords: space images; geographic information database; Bayes classifier; tree species composition; correlation analysis; космічні знімки; геоінформаційна база даних; класифікатор Байєса; породний склад дерев; кореляційний аналіз